Hearing Loss Risk Factors Analysis among Gold Mining Dozer Operators - Aisy Rahmania; Eka Rosanti; Ramadhan Saputra; Muhammad Rifki Taufik (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: industrial mining activities have the highest prevalence of NIHL due to operating a heavy vehicle. Dozer is one of the heavy vehicles with a high noise level. Methods: This study was descriptive research about risk factors related to hearing loss of 28 dozer operators at PT. X. The risk factors consisted of demographic factors, working behavior (listening to music, smoking), noise levels were analyzed with hearing loss using STS. Interviews were conducted with the workers and company representatives. Hearing loss examination used an audiometric test to determine the STS of the operators with the result that positive more than 10 dB and negative at 10 dB or less. All the data is secondary. Results: noise level of all dozers exceeds the TLV (>85dB) operated for 10 hours a day and six days a week. Half of the dozer operators had STS (+) occurred at age 40 years and older, working for more than five years, not use the PPE or misused, the habit of listening to music and smoking. Conclusion: noise and demographic factors can increase the risk of hearing loss in dozer operators. The company must control by combining plywood, foam, tray, and coir material in the dozer cabin, which can reduce 31.94 dB and apply for PPE double protection.